Assessment of the new generation aeration systems efficiency and water current flow rate, its relation to the cost economics at varying salinities for Penaeus vannamei culture. (21st February 2020) - Marappan, Jayanthi; Ambattaiyanpatti Anathaikamatchi, Balasubramaniam; Sakkarai, Suryaprakash; Thiagarajan, Ravisankar; Muthusamy, Duraisamy; Kuppusamy, Manimaran; Moturi, Muralidhar; Bera, Aritra; Ramasamy, Puthiavan; Shanmugam, Sivagnanam
Abstract: The selection of aerators and correct numbers can play an essential role in reducing the cost of production in aquaculture. The new generation aerators, namely spiral leaf, air‐jet, submersible and impeller, used in aquaculture, were assessed for its aeration efficiency and energy cost compared with the commonly used paddle wheel aerator. Of the aerators tested, the impeller had the highest aeration efficiency of 2.098 kg O2 /kW hr, followed by paddle wheel with 1.436 kg O2 /kW hr at 20‰ salinity. The spiral and air‐jet aerators had maximum aeration efficiency of 1.326 and 1.419 kg O2 /kW hr, respectively, at 35‰ salinity. The submersible aerator was not efficient as its maximum efficiency was 0.380 kg O2 /kW hr. The water flow by paddle wheel was 3 ft/sec and also provides better coverage than other types of aerators. The efficiency of aerators was high in optimum salinities (20‰ and 35‰) than the low or high saline condition. The average energy cost of shrimp pond aeration per hectare was lowest for impeller, followed by paddle wheel aerator. The study provided economic comparisons of vannamei culture using different aeration systems by keeping a uniform set of economic assumptions. Shrimp farms with impellors can give 14%–25% high returns across salinities, whereas spiral leaf can provide 5% high returns at 35‰ salinity. The combination of the type of aerators and the calculated use based on the salinity of the culture systems can result in energy‐saving and also a reduction in the production cost.